Oxidative stress damage in the protozoan parasite Trypanosoma cruzi is inhibited by Cyclosporin A - Bustos, Patricia Laura (2015)
Cyclosporin A (CsA) specifically inhibits the mitochondrial permeability transition pore (mPTP). Opening of the mPTP, which is triggered by high levels of matrix [Ca2+] and/or oxidative stress, leads to mitochondrial dysfunction and thus to cell death by either apoptosis or necrosis. In the present study, we analysed the response of Trypanosoma cruzi epimastigote parasites to oxidative stress with 5 mM H2O2, by studying several features related to programmed cell death and the effects of pre-incubation with 1 μM of CsA. We evaluated TcPARP cleavage, DNA integrity, cytochrome c translocation, Annexin V/propidium iodide staining, reactive oxygen species production. CsA prevented parasite oxidative stress damage as it significantly inhibited DNA degradation, cytochrome c translocation to cytosol and TcPARP cleavage. The calcein-AM/ CoCl2 assay, used as a selective indicator of mPTP opening in mammals, was also performed in T. cruzi parasites. H2O2 treatment decreased calcein fluorescence, but this decline was partially inhibited by pre-incubation with CsA. Our results encourage further studies to investigate if there is a mPTP-like pore and a mitochondrial cyclophilin involved in this protozoan parasite.